Three Solutions for Fourth-Order Impulsive Differential Inclusions via Nonsmooth Critical Point Theory - Dongdong Gao; Jianli Li (Journal of Function Spaces)
An existence of at least three solutions for a fourth-order impulsive differential inclusion will be obtained by applying a nonsmooth version of a three-critical-point theorem. Our results generalize and improve some known results.